Research on Testing Methods of Life Detection Equipment for Water-bearing Soil Disasters - Nan Yanyun; Yan Jin; Xie Shizhe (E3S Web of Conferences, 2025)
Aiming at the current water-bearing soil disaster life detection equipment testing research is relatively small, mainly relying on key components and equipment as a whole of the factory test, the lack of standardised system testing problems, this paper designs the water-bearing soil disaster life detection equipment comprehensive performance testing methods and testing process. We combine the equipment with the actual application scenarios, analyse the equipment testing requirements, determine the equipment testing content and testing methods, and establish a standardised testing process. The establishment of standardised test methods is of great importance in assessing the overall capability of the equipment and improving its effectiveness and reliability in complex disaster environments.